An Observation‐Based Correction for Aerosol Effects on Nitrogen Dioxide Column Retrievals Using the Absorbing Aerosol Index - Matthew J. Cooper; Randall V. Martin; Melanie S. Hammer; Chris A. McLinden (Geophysical Research Letters)
Abstract Retrievals of nitrogen dioxide (NO2) and other trace gases from satellite measurements rely on accurate calculation of an air mass factor (AMF) to account for the atmospheric light path. Scattering and absorption of sunlight by aerosols affects AMFs by impacting the sensitivity of satellite‐observed radiances to NO2 at different altitudes. Current NO2 retrievals either do not explicitly account for these effects or rely on aerosol information from an external source. Here we investigate a method for quantifying the impact of aerosols on NO2 AMFs using the Absorbing Aerosol Index, a satellite‐based measure of light absorption and scattering by aerosols. We find a robust relationship between the Absorbing Aerosol Index and the aerosol correction to NO2 AMFs using the GEOS‐Chem chemical transport model and the LIDORT radiative transfer model. This relationship enables estimating the impact of aerosols on AMFs using observed Absorbing Aerosol Index values, thus yielding an observation‐based aerosol correction for NO2 retrievals.